AKURASI DIAGNOSTIK RAPID DIAGNOSTIC TEST METODE DETEKSI ANTIBODI DALAM MENDETEKSI CORONAVIRUS DISEASE 2019: Systematic Review - Tiara Josephine Gracienta (2021)
Coronavirus disease 2019 (COVID-19) is a respiratory tract infection caused by a new type of coronavirus, Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2). A fast, accurate, and affordable diagnostic method is needed to overcome its rapid transmission. Rapid Diagnostic Test (RDT) is considered a practical test kit in this pandemic situation. The purpose of this study was to determine the diagnostic accuracy of antibody detection RDTs in detecting COVID-19, which includes sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV). This is a systematic review with a pooled data analysis. Data was collected through literature searches on four different databases using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) 2015. This systematic review included all relevant articles from January-August 2020. Twenty-four studies met the inclusion criteria. The results showed that the IgM or IgG detection method had the highest sensitivity and NPV of 72.42% (95% CI, 71.15-73.67%) and 73.30% (95% CI, 72.39-74.19%), respectively. The IgG detection method had the highest specificity and PPV of 96.70% (95% CI, 96.13-97.21%) and 95.75% (95% CI, 95.04-96.36%), respectively. Based on the diagnostic accuracy, RDT is not recommended as a primary diagnostic test, but it has utilities in screening and serological surveillance.